ROLE OF NURSES IN COMMUNITY HEALTH PROMOTION AS NURSING STUDENTS PERCEIVE AND PRACTICE - Hadjo, Samuel S; Kasenda, Telvie L (-, 2015)
Introduction Nursing encompasses autonomous and collaborative care of individuals of all ages, families, groups and communities, sick or well and in all settings. Nursing includes the promotion of health, prevention of illness, and the care of ill, disable and dying people. Aim This study purposes to analyze the studentâs opinion and practice toward community health promotion Method Mixed method research design is used involving observational and quasi-experimental design, based in the data collected of both qualitative and quantitative as well. There were in total 48 students and 115 communities participated using purposive sampling method. Conclusion Half of respondent define health promotion is part of delivery information and education regarding health. More than half students agree where health education focuses on educating health on the other hand health promotion involves more activities and programs that improve health. The three top categories are maintain environmental health, followed by practice health education and perform some health screening activities. Finally, community health nursing promotion has a significant effect on knowledge, attitude of CHBs among the household settings.